2013
DOI: 10.1002/jcb.24445
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein protects against cardiac hypertrophy through blocking MEK‐ERK1/2 signaling

Abstract: Baicalein, a flavonoid present in the root of Scutellaria baicalensis, is well known for its antibacterial, antiviral, anti-inflammatory, antithrombotic, and antioxidant effects. Here we show that baicalein also attenuates cardiac hypertrophy. Aortic banding (AB) was performed to induce cardiac hypertrophy secondary to pressure overload in mice. Mouse chow containing 0.05% baicalein (dose: 100 mg/kg/day baicalein) was begun 1 week prior to surgery and continued for 8 weeks after surgery. Our data demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 25 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…Here we show that baicalein attenuated cell death, apoptosis, and [Ca 2+ ]i accumulation of H9c2 cells caused by lysoPC in a dose-dependent manner. Our results are in line with recent investigations showing that baicalein protects against balloon injury-induced intimal hyperplasia and aortic banding-induced cardiac hypertrophy and fibrosis [16,17]. Therefore, baicalein might have the therapeutic utility in the treatment of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 92%
“…Here we show that baicalein attenuated cell death, apoptosis, and [Ca 2+ ]i accumulation of H9c2 cells caused by lysoPC in a dose-dependent manner. Our results are in line with recent investigations showing that baicalein protects against balloon injury-induced intimal hyperplasia and aortic banding-induced cardiac hypertrophy and fibrosis [16,17]. Therefore, baicalein might have the therapeutic utility in the treatment of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 92%
“…H9c2 rat heart cell is a subclone of the original clonal cell line derived from embryonic BD1X rat heart tissue [53]. Recently, H9c2 is commonly used to investigate the mechanisms underlying the pathophysiology of cardiomyopathy including cardiac fibrosis [54][55][56][57]. In this study, we demonstrated that IS stimulated the CB1R mRNA expression in neonatal mice cardiac fibroblast that is consistent with the expression pattern observed in H9c2 cells.…”
Section: The Limitation Of Studysupporting
confidence: 89%
“…The premise of this observation emerges from the fact that the activation of phosphorylated ERK1/2 is crucial for cellular hypertrophy. This is supported by the finding that angiotensin II induced cellular hypertrophy in H9c2 cells through ERK1/2 but not p38 or JNK (Zong et al 2013). Of particular interest in this study, baicalin, LOX inhibitor, blocked the cellular hypertrophy effect of angiotensin II through ERK1/2 signaling pathway (Zong et al 2013).…”
Section: Discussionsupporting
confidence: 56%